Sistem Prediksi Kelayakan Rental Mobil Menggunakan Algoritma C4.5 - Siti Aminah; Febriansyah Febriansyah (JURIKOM (Jurnal Riset Komputer), 2021)
The purpose of this study is to build a system that can predict the feasibility of prospective car rental service users. It is not easy for car rental service providers to determine which consumers can use car rental services, with procedures that are still manual and it is difficult to obtain user data information. To be able to predict the feasibility of car rental service users, it is necessary to use an information system that can predict whether users are eligible or not. This research uses the waterfall system development method. The waterfall method has several stages, including analysis, design, coding and testing. The results of the research obtained from the feasibility test of the feasibility prediction system for car rental service users using algorithmic 4.5 that the results of the alpha test were tested for the feasibility of the system with an overall value of 3.6 by system that has been made feasible to use